Esg And Green Marketing Practices In Consumer Electronics Retailing : A Configuration Framework Model (International Journal of Environmental Sciences, 2025)
The prosperity of any business is dependent on its marketing efforts. Environmental, social, and governance (ESG) investing, along with green marketing targeted at consumer electronics, presents a fresh viewpoint on harmonizing these opposing priorities. Modern brand management and marketing strategies were established in the 1950s by Procter & Gamble, General Foods, and Unilever in response to product innovations from their competitors. The competitive strategies and advantages of the company are outlined in its strategic framework and its approach to ESG issues. The strategy of the firm acts as the blueprint for how senior management intends to reach its goals. A company strategy is characterized as the all-encompassing method for attaining an ideal future condition. Competitive strategy focuses on achieving distinctiveness, as described by Porter in his 1996 Harvard Business Review article (1). He claims that it entails choosing a different combination of value-adding activities. Marketers are continually searching for creative ways to boost revenue. Customer data is utilized to refine existing offerings and develop new ones. To convey value, marketing devises distribution and communication strategies. Companies implement various strategies to market their products, including Green Practices and ESG initiatives. This paper explores green practices in business and retail environments, highlighting the importance of ESG investing over time, especially for electronic companies. A conceptual model is presented based on observational studies regarding green practices, with a focus on ESG considerations.